An elastic carbon layer on echeveria-inspired SnO2 anode for long-cycle and high-rate lithium ion batteries - Kim, A-Young; Kim, Jung Sub; Hudaya, Chairul; Xiao, Dongdong; Byun, Dongjin; Gu, Lin; Wei, Xiao; Yao, Yuan; Yu, Richeng; Lee, Joong Kee (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The commercialization of Sn-based anodes for lithium ion batteries is still hindered due to the inherent volume change leading to a rapid capacity fading during the electrochemical cycle. Inspired by echeveria, a plant that stores sufficient water in its hierarchical leaves to survive in a drought, we report a breakthrough by designing the hierarchical and nanoporous SnO2 electrode encapsulated with ultrathin carbon layer (similar to 2 nm). As evidently captured by in situ transmission electron microscopy, the conformal carbon coating on the surface of anode may provide an elastic cover that suppresses the cracks due to severe volume change, and increases both electrical and ionic conductivity, allowing the cells to exhibit excellent lithium storage performance with more than 800 cycles even with relatively high-rate of current densities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: ELECTROCHEMICAL PERFORMANCE; HIGH-CAPACITY; COATED SNO2; GRAPHENE; COMPOSITE; GRAPHITE; NANOTUBE; STORAGE; NANOPARTICLES; MICROSPHERES